Association of the time interval between first and last birth with obesity in middle-aged postmenopausal Chinese women: a cross-sectional study in southern China - Su, Zhenzhen; Luo, Yanfang; Ye, Fen; Xu, Jiahui; Lu, Hui; Zhu, Lingyun (Frontiers in Medicine, 2025)
BackgroundBirth interval is acknowledged as a significant factor affecting the health of women and their children. This study aimed to investigate the relationship between the time interval from the first to the last birth and the prevalence of general obesity, abdominal obesity, or both, among middle-aged postmenopausal Chinese women.MethodsThis cross-sectional survey examined 4,799 Chinese postmenopausal women, aged 45–59 years, who had at least one live birth. General obesity was assessed using body mass index (BMI), while abdominal obesity was evaluated through waist-to-hip ratio (WHR), waist-to-height ratio (WHtR), and waist circumference (WC). Multivariate linear and logistic regression models were employed to analyze the associations between the time interval from the first to the last birth and obesity.ResultsThe values of all four obesity measures increased with a longer time interval between the first and last births (P for trend <0.001). After adjusting for potential confounding variables, women with an interval of 10 or more years between their first and last birth exhibited a prevalence of obesity that was 1.49 times (95% confidence interval [CI], 1.12–1.99) higher by BMI, 1.29 times (95% CI, 1.02–1.61) higher by WC, 1.23 times (95% CI, 1.04–1.69) higher by WHtR, and 1.50 times (95% CI, 1.01–2.12) higher by WHR when compared to those with a 0 to 1-year interval.ConclusionThe time interval between the first and last birth was positively associated with an increased risk of obesity, particularly abdominal obesity, in middle-aged postmenopausal Chinese women. Therefore, healthcare providers should prioritize reproductive health issues among women, actively promote appropriate birth intervals, and advocate for evidence-based pregnancy planning for women of childbearing age. Moreover, these research findings offer valuable scientific insights for policymakers, enabling them to develop more targeted obesity prevention and management strategies specifically tailored to this demographic group.